Plan de negocios para la creación de una microempresa de marketing digital para el sector turístico en la ciudad de Latacunga. - Caisaguano Sangopanta, Eliana Jissela (2019)
Business plan for the creation of a digital marketing micro enterprise for the hospitality industry in Latacunga, aims to determine the feasibility of entering a market segment in which technology is changing the dynamics of the strategies of marketing for sale and promotion of products and services, promoting B2B business models. For this purpose, four objectives were raised that allowed to analyzethe theoretical references on digital marketing and B2B business models, to the market study to analyze supply and demand, to the technical, financial and profitability evaluation study. Documentary analysis and the survey methods were used, which was aimed at tourism companies, demonstrating that there is ignorance about digital marketing strategies and that there is a predisposition to implement them in their businesses. In the technical study, it was defined the profiles of the people required to provide quality services, as well as the flows of each process. The profitability evaluation showed an IRR of 27.40%, NPV of USD 17,162.26, cost benefit ratio 1.32; so it can be concluded that the project is viable.